PbsB Regulates Morphogenesis, Aflatoxin B1 Biosynthesis, and Pathogenicity of Aspergillus flavus - Yuan, Jun; Chen, Zhong; Guo, Zhiqiang; Li, Ding; Zhang, Feng; Shen, Jiaojiao; Zhang, Yi; Wang, Shihua; Zhuang, Zhenhong (Frontiers in Cellular and Infection Microbiology, 2018)
As an opportunistic pathogen, Aspergillus flavus is one of the major causes of food contamination around the world. In this study, pbsB gene knockout mutant (ΔpbsB) and pbsB overexpression strain (OE) of A. flavus were constructed by homologous recombination. The results showed that the mycelia growth, conidiation and the formation of sclerotia in ΔpbsB mutant were significantly suppressed, and up-regulated in OE strian compared to wild-type strain (WT). Q-PCR analysis showed that PbsB regulated the sclerotia formation through sclerotia related gene nsdC. With TLC and qRT-PCR analysis, it was found that PbsB up-regulated the bio-synthesis of aflatoxin B1 (AFB1) through regulatory gene aflR and structural gene aflC, aflD, aflK, and aflQ in the aflatoxin gene cluster. In osmotic stress response analysis, ΔpbsB mutant was significantly more sensitive to osmotic pressure with 1.2 mol/L sorbitol, compared to WT and OE strains. In virulence analysis, the infection capacity of ∆pbsB strain to peanut and maize kernels decreased dramatically, and significantly fewer spores and lesser mycelia were produced in ∆pbsB strain on the surface of peanut and maize kernels, and the infection capacity of OE strain to kernels increased significantly compared with WT strain. The AFB1 bio-synthesis ability of A. flavus in crop invasion models was also found to be coincide with the expression level of pbsB. All the results of the study shows that, as a MAPKK, PbsB is critical for growth and virulence in A. flavus, and lay a theoretical foundation for the prevention and control of A. flavus contamination.